Studi Angkutan Pekerja Di Kawasan Industri Sebagai Salah Satu Upaya Mengurangi Kemacetan Di Kota Semarang - Albert Setyo Handoko; Elrangga Sadewa Nugroho; Rudatin Ruktiningsih (Universitas Katolik Soegijapranata Semarang, 2019)
Industrial estates have a large scale workforce. Workers usually come from different locations, so they need transportation to get to the Industrial Estate location, because of the large movements of industrial workers. Especially at the turn of the morning and evening work shifts, at these hours the number of vehicle workers contributes to traffic congestion on the roads it passes. The survey was conducted at the entrance of the industrial area to determine the level of congestion that occurred at the entrance of the Industrial Zone road section, namely on the Kaligawe road, Jalan Candi Raya, Jalan Pantura Semarang - Kendal KM.12 especially when there was a shift of work shifts in terms of road capacity based on the Indonesian Road Capacity Manual. To determine the level of congestion if after provided worker transportation. From the data obtained, the largest VCR results in the Wijayakusuma Industrial Zone are 3.177 pcu / hour when the entry hours from the direction of Kendal are classified as the most jammed; in the Terboyo Industrial Zone is 0.917 pcu / hour when the hour enters from the direction of Demak; in the Temple Industrial Area is 0.875 pcu / hour when the hours go out towards Semarang are classified as quiet. After the workers of private vehicle users are transferred using buses, the largest VCRs are obtained from Type A buses with a capacity of 25 passengers, thus the value of VCRs in the Wijayakusuma Industrial Zone is 0.188 pcu / hour in the direction of Kendal; in the Terboyo Industrial Area is 0.066 pcu / hour in the direction of Demak; in the Temple Industrial Zone is 0.122 pcu / hour in the direction of Semarang. Planning to determine the number of buses that must be provided for each Industrial Estate, as well as efficient bus operating time.